Influence of various heat treatment procedures on the corrosion behavior of Al-Zn-Mg-Cu alloys - Kumar, Neeraj; Dwivedi, Deepak; Sharma, Ashutosh; Ahn, Byungmin; Manoj, M. K. (Materials Research Express, 2019)
In this study, we have investigated the effect of different heat treatment sequences on the microhardness and corrosion resistance of Al-Zn-Mg-Cu. Five different heat treatment sequences include water quenching, solution heat treatment (SHT), and re-aging (RA) treatment for different times (0.5 h, 0.7 h, and 0.9 h). The microstructural analysis reveals the formation of a higher amount of precipitates in RA0.7 h sample while the least amount of precipitates were noticed for SHT sample. SHT dissolves most of the precipitates present in the alloys as confirmed from the microstructural analysis. The maximum value of hardness and yield strength (YS) were estimated for RA0.7 h and SHT treated samples, respectively. The electrochemical analysis depicted the lowest corrosion rate for RA0.9 h followed by SHT sample whereas the highest corrosion rate was noticed for T6 treated sample. It is also noteworthy that the corrosion rate of RA0.7 h is higher than the RA0.9 h among re-aged samples. The importance of heat treatment cycle for optimizing the mechanical and electrochemical performance of Al-Zn-Mg-Cu alloys under harsh conditions are also discussed.
Keywords: Al -Zn-Mg-Cu alloys; Al7075; Corrosion behavior; Electrochemical analysis; Electrochemical performance; Heat treatment cycle; Microstructural analysis; Solution heat treatment; aging; Al7075; corrosion; microhardness; quenching; solution heat treatment